Malaysia’s 13th general election in Sabah: factors determining the winners - Mohd Hamdan Haji Adnan (Penerbit UKM, 2013)
Sabah voters in the 13th Malaysian General Election were considered a Barisan Nasional (BN) “fixed deposit” and Prime Minister Najib Tun Razak had proclaimed that his party would actively work on enhancing this edge to sustain their dominance. Pakatan Rakyat (PR), of the opposition coalition acknowledged the threat and took steps to neutralise it. Initially, the opposition parties believed that they had a fifty percent chance or more to capture Sabah to form both the State and Federal governments and, on reading contemporary discussions in the social media, it is easy to see why. However, the main stream media persisted in promoting the government as a sure winner and, as GE 13 drew nearer, the tide changed to favour BN. This paper determines the strategies and issues that proved to be effective in winning state and parliamentary seats in Sabah.. Further, it investigates the impact of the Suluk incursion in Lahad Datu on the election, seeking to discover how the political parties involved exploited and benefited from this tragic incident. Finally, this paper explores the people who were instrumental in influencing the tide of change in Sabah’s GE 13.